2006
DOI: 10.1055/s-2006-948555
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Functions in Follicle Maturation

Abstract: The extracellular matrix (ECM) promotes and/or inhibits many cellular processes, including but not limited to proliferation, differentiation, and survival, which must occur for follicle growth and oocyte maturation. The ECM regulation of cellular processes in ovarian cells is being investigated in many animal models, including avian, rat, bovine, porcine, rabbit, sheep, human, and mouse. Granulosa cells are more frequently employed; however, the culture of intact follicles and ovaries has been developed and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 69 publications
4
79
0
3
Order By: Relevance
“…Previous works by others have shown that extracellular matrices such as Matrigel can have beneficial effects on ovarian follicle culture, granulosa cell communication, proliferation, survival, and steroidogenesis in vitro in various species [24]. We first studied the differentiation of SSCs into ovarian-cell-like cells in the presence of Matrigel.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works by others have shown that extracellular matrices such as Matrigel can have beneficial effects on ovarian follicle culture, granulosa cell communication, proliferation, survival, and steroidogenesis in vitro in various species [24]. We first studied the differentiation of SSCs into ovarian-cell-like cells in the presence of Matrigel.…”
Section: Resultsmentioning
confidence: 99%
“…However, even in the presence of LIF, these cells cultured in monolayers gradually lose their functional characteristics such as production of cytochrome P450-aromatase and FSHR. Similarly, during spontaneous luteinization of GCs in vitro, the initially globular GCs progressively lose their ability to express not only aromatase and FSHR but also type IV collagen (Coll IV) (6), the principal component of the extracellular matrix (ECM) (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The basal lamina excludes blood vessels and nerves from the GCoocyte unit until after ovulation and, unlike the zona pellucida, is not traversed by any cells or cell processes (Rodgers et al, 2003). In a wide variety of tissues, basal laminae provide support and anchorage for polarised epithelial cells and also regulate their behaviour (cell shape, proliferation, apoptosis, differentiation and migration) (Berkholtz et al, 2006b;Monniaux et al, 2006). A direct transmembrane link between the ECM and the actin cytoskeleton is provided by integrins, which are expressed in the ovary and have a significant role in the regulation of cell behaviour in a wide range of tissues Monniaux et al, 2006).…”
Section: Introductionmentioning
confidence: 99%